Human Resources Development In Bitung City Library Service - Kalangit, Welmi; Masengi, Evi Elvira; Pangkey, Itje; Mandagi, Marthinus (Technium Social Sciences Journal, 2022)
This study aims to analyze Human Resource Development at the Bitung City Library Service. This study uses qualitative research methods. There are 6 (six) informants who were interviewed. The current research results indicate that technical guidance activities are virtual and face-to-face. Technical guidance activities are only carried out 2 (two) times a year for the Bitung City Library Service. The level of education of employees is still not by the positions and competencies required. There is still no librarian, and the achievement of work results from employees who have received training is not optimal. Even the existing facilities and infrastructure at the Bitung City Library Service are still inadequate. The Bitung City Library Service does not yet have educational backgrounds or disciplines about libraries. The service has not yet maximized the impact felt by the service on employees who have received socialization related to the main tasks and functions. There is no reading building for the public at the Bitung City Library Service. There is still no archivist, so there is still a lack of human resources at the Bitung City Library Service. Employees are still not able to complete tasks quickly and accurately. Suggestions from researchers are that the implementation of technical guidance activities must be added and maximized. The level of employee education must be by the positions and competencies required.